Potato chips with flavours: accuracy of the nutritional labelled information - Albuquerque, T.G. (2018)
Introduction and aim: The nutrition declaration presents information that should allow consumers to make an informed choice. Regulation (EU) No. 1169/2011 sets definitions, principles and procedures regarding the information provided on the labels of pre-packaged foods among the European Union (EU) Member States. Tolerances for nutritional labelling have been established in the EU food legislation framework. The aim of this study was to evaluate the compliance between the declared and analysed values for potato chips with flavours, considering the permitted tolerance limits for salt, fat and saturated fatty acids (SFA). Methods: Between 2015 and 2016, 14 types of flavoured potato chips were acquired in supermarkets from Lisbon region. Afterwards, the information from the nutrition declaration of the label was registered. Then samples were analysed regarding their salt, total fat and fatty acids composition. The obtained analytical values were compared with the declared ones and the compliance checked considering the limits fixed by legislation. Results: Regarding total fat, only one sample of the analysed foods had a declared value outside the tolerance limits whereas for salt and SFA, three products of each were outside the tolerance limits (n=3, 21%). However, for two of these products, the analytical value for salt content was higher than the upper tolerance limit. Conclusion: The obtained results can be noteworthy for consumers, public health organizations, and food industries. However, the results of the analysed potato chips fully justify the extension of this study to other categories of pre-packaged foods, but also to develop efforts with industry to carefully follow this situation and to provide reliable and accurate nutrition declarations.